L-Thyroxine Attenuates Pyramidal Neuron Excitability in Rat Acute Prefrontal Cortex Slices - Cao, James H.; Pan, jinhong; Lin, Hung-Yun; Davis, Faith B.; Zhou, Min; Davis, Paul J. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
Acute modulation of ion channel function by a nongenomic mechanism initiated at the plasma membrane is a newly appreciated action of thyroid hormone. However, whether thyroid hormones at physiological concentrations contribute to the setting and dynamic regulation of basal activity of neuron excitability in the mammalian central nervous system is an issue that is not yet well-understood. In this study, we used acute prefrontal cortex (PFC) slices of the young adult rat (6-8 weeks) to explore the action of L-thyroxine (T4) on the excitability of layer V-VI pyramidal neurons. In the basal state of the brain slice model, blood vessel thyroid hormone content was removed prior to study, so that exposure to a bath solution containing T4 may allow identification of rapid-onset effects of T4 on neuronal excitability. Such rapidonset effects are nongenomic in mechanism. We show that in whole-cell current clamp recordings, 18/23 pyramidal neurons responded electrophysiologically to a 3 min bath application of T4 (5-37.5 nM as directly-measured free hormone). Among the T4-responsive neurons (18/23 cells), 94% showed an average 12.4 mV membrane potential (Vm) depolarization and 72% showed an average spike of 45%. These results indicate that T4 can rapidly modulate neuronal excitability.
Keywords: rat pre-frontal cortex